Obtaining the solid solution Sb2S3-xSex by selenization of Sb2S3 film and identifying the thermal processing parameters to achieve recrystallization while maintaining phase-purity. (15th November 2021) - Flores-Ventura, O.; Courel, Maykel; Sanchez, T.G.; Mathews, N.R.; Mathew, X.
Abstract: In this work, thin films of the ternary material Sb2 S3-x Sex with promising optical and electrical properties were developed for its application as absorber material in photovoltaic devices. It was found that 400 °C is the lowest recrystallization temperature at which phase-pure polycrystalline films of Sb2 S3-x Sex can be obtained. Films were recrystallized in a mixture of S/Se vapor by varying the proportion of Se and the film properties were studied as a function of Se content. The conductivity and photosensitivity were increased with the increase in the amount of Se in films. The activation energies associated with the defects or traps in the films decrease with the amount of Se. The morphology of the film changes significantly depending on the annealing pressure. Films recrystallized in an ambient of S/Se vapor generated from 10 mg each of S and Se at 400 °C and 460 Torr pressure are found to have the optimum band gap, highest photosensitivity, and phase-purity. Assuming an appropriate window layer, the modeling result shows that the obtained film Sb2 S0.6 Se2.4 has the suitable material properties that can result in solar cells with efficiencies in the range of 27%.